Right derivations on ordered semigroups - M. Murali Krishna Rao (Journal of Hyperstructures, 2019)
Over the last few decades, several authors have investigated the relationship between the commutativity of ring R and the existence of certain specified derivations of R. In this paper, we introduce the concept of right derivation on semigroups and we study some of the properties of right derivation of semigroups. We prove that if d be a non-zero right derivation of a cancellative ordered semigroup M, then M is a commutative ordered semigroup.